Determinants of student interest in using financial technology: A Theory of planned behavior approach - Kurniawan, Marzuliandra; Pratami, Andini; Ramadhani, Elsa; Ramashar, Wira (President University Press, 2024)
This research was conducted to measure and determine the determinants of student interest in using financial technology, this is important to see the behavior of using financial technology in digital transactions today. This research is empirical research by means of a survey with the type of data collected through questionnaires. The sample size is 400 students. The sampling technique used is accidental sampling. The results showed that students' interest in using financial technology is significantly influenced by attitudes, while subjective norms have no effect on students' interest in using financial technology. Meanwhile, perceived behavioral control has a significant effect on students' interest in using financial technology, and perceived risk has no effect on students' interest in using financial technology.